Nutritional and Sensory Properties of Protein Hydrolysates Based on Salmon (Salmo salar), Mackerel (Scomber scombrus), and Herring (Clupea harengus) Heads and Backbones - Aspevik, Tone; Steinsholm, Silje; Vang, Birthe; Carlehög, Mats; Arnesen, Jan Arne; Kousoulaki, Katerina (Frontiers in Nutrition, 2021)
Protein hydrolysates based on salmon, mackerel and herring heads and backbones were produced and the sensory properties of the hydrolysates were evaluated by a highly trained sensory panel. The nutritional content of the products was evaluated, and the hydrolysates contained all amino acids inherent to the raw material, including considerable levels of connective tissue amino acids glycine, proline and hydroxyproline. Hydrolysates based on herring were the most flavour intense, whereas hydrolysates based on salmon were deemed more palatable. In this study, choice of fraction (heads vs backbones) and enzyme had minor effects on sensory and nutritional properties, indicating that choice of raw material specie was the major factor for flavour development in the produced protein hydrolysates. There were large variations in protein content and amino acid composition in the raw material fractions, but as expected, only minor variations were found in the final products.